Optimalisasi Kepuasan Konsumen: Dinamika Strategi Bauran Pemasaran dalam Industri Properti Perumahan - anas, Khoiruddin; Chairul Anam (PT. PENERBIT TIGA MUTIARA, 2023)
To maximize customer satisfaction through marketing strategies residential property companies must understand the dynamics of appropriate marketing strategies. One of them is by maximizing consumer satisfaction with several important factors such as product, price, promotion and place. The aim of this research is to analyze the influence of the marketing mix on consumer satisfaction at Astapada Indah III Jombang housing. This type of research uses quantitative research with a cross-sectional study approach. The population of all residents of the Astapada Indah III housing complex was 68 and the sample was 58 people using incidental sampling technique. The independent variables are product, price, promotion, place and the dependent variable is consumer satisfaction. The research instruments used questionnaires, data processing using multiple linear regression tests. The results of the research showed that product and location had a significant effect on housing consumer satisfaction, while price and promotion had no effect on consumer satisfaction. However, simultaneously product, price, promotion and location all influence consumer behavior simultaneously by 79.4%.